Adhesion of silicone oil and emulsification: an in vitro assessment using a microfluidic device and 'Eye‐on‐a‐Chip'. Issue 3 (28th November 2018) - Lu, Yongjie; Chan, Yau Kei; Lau, Long Hei; Chao, Youchuang; Shih, Kendrick Co; Lai, Shiu Ming; Wong, David; Shum, Ho Cheung
Abstract: Purpose: Silicone oil (SiO) with additives of high‐molecular‐weight (HMW) SiO molecules, eases both the injection and removal. When used inside an eye, it remains unclear how increasing extensional viscosity of SiO might reduce emulsification. Using cell‐lined models, this study aims to understand the reason why SiO with HMW is less prone to emulsification. Methods: The adhesion of SiO was studied and recorded in a cell‐coated microchannel by optical microscopy. The resistance of SiO against emulsification was tested on another cell‐coated eye‐on‐a‐chip platform, which was subject to simulated saccadic eye movements, for 4 days. Silicone oil (SiO) candidates with HMW, SiOHMW 2000 and SiOHMW 5000, and their counterparts SiO2000 and SiO5000 without HMW, were tested. The quantity of the SiO emulsified droplets formed was assessed daily by optical microscopy. Results: When flowing in the microchannel, SiO adheres on the cell‐coated substrate. The number of droplets is generally lower in SiO with HMW than their counterparts. At the end of the experiment, the average numbers of droplets in SiO2000 (29.1 ± 41.0) and SiO5000 (9.1 ± 19.5) are higher than those in SiOHMW 2000 (6.0 ± 4.5) and SiOHMW 5000 (5.6 ± 4.1). Conclusion: A new mechanism of emulsification of SiO is proposed: SiO adheres to ocular tissue to form emulsified droplets. The presence of HMW, which increases the extensional viscosity, may resist the break‐up of SiO from the substrate to form emulsified droplets. When tested in a physiologically representative platform, the use of HMW in SiO generally reduces the number of droplets formed in vitro .